FEATURES OF CLINICAL AND DIAGNOSTIC CHANGES IN CORONARY HEART DISEASE (World Bulletin of Public Health, 2023)
Purpose of the study. To study the relationship of ischemic changes on the ECG with the duration of the pain syndrome. Materials and methods. The study was conducted in polyclinics and clinics in Bukhara. The survey included 1332 people complaining of pain in the chest and in the left arm. 167 people were diagnosed with coronary artery disease. Moreover, on the ECG taken at rest in 117 patients with coronary artery disease, ischemic changes were detected, and in 50 patients such changes were not detected. The average age of the surveyed was 51.7+2.6 years. ECG was taken on a 6-NEK electrocardiograph at rest in 12 conventional leads Results
Keywords: chest pain; ischemic changes; ischemic heart disease